Harmonizing Linguistics with Melody: An Analysis of Lexemic Idioms in Taylor Swift's 'Evermore' and Their Pedagogical Implications for EFL - Marpaung, Tiara Septinia; Pangaribuan, Rotua Elfrida; Pasaribu, Donna Ria (ELT Worldwide: Journal of English Language Teaching, 2023)
Lexemic idioms refer to phrases or expressions that possess a distinct meaning that surpasses the literal interpretation of their constituent words. This study examines the lexemic idioms present in the lyrics of songs from Taylor Swift's Evermore album. This study employs a qualitative descriptive methodology, drawing on Makkai's (1972: 135-178) theoretical framework, which categorizes idioms into two distinct types: lexemic and sememic idioms. The concept of lexemic idiom can be classified into six distinct types. The topic of discussion pertains to phrasal verbs and idiomatic expressions. Idiomatic expressions... The concept of irreversible binominal idioms is being discussed. The topic under consideration pertains to phrasal compound idioms. Utilizing verb idioms… The objective of this study is to identify and analyze the many types of lexemic idioms included in the lyrics of the record, with the aim of determining their respective meanings. The objective of this analysis is to elucidate the proficient utilization of idiomatic expressions by Taylor Swift in effectively conveying her thematic and emotional intentions, encompassing the realms of love, grief, nostalgia, and hope. The study yielded a total of 95 lexemic idioms, which have been categorized based on their respective types and forms. The distribution of idioms in the given text is as follows: 14 idioms of phrasal verbs (14.74%), 45 idioms of tournure (47.37%), 8 idioms of irreversible binomials (8.42%), 23 idioms of phrasal compounds (24.21%), and 5 idioms incorporating verbs (5.26%). No instances of pseudo-idioms were identified within the song lyrics of Taylor Swift's album evermore. The predominant categories of lexemic idioms in the lyrics of Taylor Swift's songs on the evermore album, when considering the percentage of the entire data, indicate that tournure idioms exhibit the most dominance compared to other types. Furthermore, the study's implications for English as a Foreign Language (EFL) pedagogy introduce an innovative approach to teaching, suggesting the integration of popular song lyrics for a more holistic language learning experience. This research not only contributes a fresh perspective to the field of linguistics but also underscores the profound impact of idiomatic expressions on language, culture, and emotion.